Characterization of a recurrent missense mutation in the forkhead DNA-binding domain of FOXP1. Issue 1 (December 2018) - Johnson, Tyler; Mechels, Keegan; Anderson, Ruth; Cain, Jacob; Sturdevant, David; Braddock, Stephen; Pinz, Hailey; Wilson, Mark; Landsverk, Megan; Roux, Kyle; Weimer, Jill
Abstract Haploinsufficiency of Forkhead box protein P1 (FOXP1), a highly conserved transcription factor, leads to developmental delay, intellectual disability, autism spectrum disorder, speech delay, and dysmorphic features. Most of the reported FOXP1 mutations occur on the C-terminus of the protein and cluster around to the forkhead domain. All reportedFOXP1 pathogenic variants result in abnormal cellular localization and loss of transcriptional repression activity of the protein product. Here we present three patients with the sameFOXP1 mutation, c.1574G>A (p.R525Q), that results in the characteristic loss of transcription repression activity. This mutation, however, represents the first reportedFOXP1 mutation that does not result in cytoplasmic or nuclear aggregation of the protein but maintains normal nuclear localization.